Desing of wind propellers for horizontal axis - Albadan Molano, David Esteban; Salamanca Céspedes, Jorge Enrique; Gallego Torres, Adriana Patricia (Universidad Pedagógica y Tecnológica de Colombia, 2018)
1 recurso en línea (páginas 119-126).